Security of smart home-smartphones systems - Teixeira, Diogo (2020)
With technology increasingly present in people’s lives, smart homes are gaining more and more impact each day. While in the past smart homes consisted in presence sensors, cameras and automatic shutters, nowadays they are composed of several sensors and equipment that can control and monitor different things, such as temperature or heat. The homeowners want to control and monitor their home through applications on their smartphone which contributed to the smart homes-smartphones system concept. These are systems that control people’s privacy, so various security mechanisms must be implemented to mitigate vulnerabilities. In this paper we present main vulnerabilities of these systems and main proposals to mitigate threats.